METHOD OF FORECASTING THE TERMS OF SETTLING OF STRUCTURES ON SOILS WITH SILT LAYERS - Oksen, Yevhen (Academic journal Industrial Machine Building Civil Engineering, 2019)
The method of forecasting the size and timing of sedimentation of structures on soils with silt layers, based on the results offield observations, has been developed. It is suggested to use a set of exponential dependencies with a constant component.The algorithm and software for calculation of the envelope by experimental data by a stepwise approximation are developed.The process of consolidation of soils is considered as a combination of simultaneous and independent flow of phases of primary filtration consolidation and secondary consolidation of creep. According to the results of data processing of observations by direct iterative calculations by finding the minimum nonconnectedness by the method of least squares.
Keywords: base; silt; structure; precipitation; forecast; size; term; method; calculation